Reelin has antidepressant-like effects after repeated or singular peripheral injections. (15th June 2022) - Allen, Josh; Romay-Tallon, Raquel; Mitchell, Milann A.; Brymer, Kyle J.; Johnston, Jenessa; Sánchez-Lafuente, Carla L.; Pinna, Graziano; Kalynchuk, Lisa E.; Caruncho, Hector J.
Abstract: Chronic stress is a significant risk factor for depression onset. The effects of chronic stress can be studied preclinically using a corticosterone (CORT)-administration paradigm that results in a phenotype of depressive-like behavior associated with neurochemical abnormalities in brain regions like the hippocampus. We have recently shown that intrahippocampal infusions of Reelin have a fast effect in normalizing CORT-induced behavioral and neurochemical alterations. Reelin is also expressed in multiple peripheral systems and is found in blood plasma which prompted us to investigate whether peripheral intravenous (i.v.) Reelin injections could also result in antidepressant (ATD)-like actions. Repeated i.v. injections of Reelin were effective in rescuing the CORT-induced increases in forced-swim-test immobility in male and female rats, decreases in Reelin-immunopositive cells in the dentate gyrus subgranular zone, the expression of hippocampal GABAA β 2/3, GluA1, and GluN2B receptors, and serotonin transporter (SERT) membrane protein clustering (MPC) in blood lymphocytes. However, Reelin had only a partial effect on the number and maturation rate of dentate gyrus newborn cells. CORT and Reelin did not affect open field test behavior. After evaluating the effects of multiple Reelin injections, we demonstrated that a single Reelin injection administered at the end of CORT treatment could rescue in 24 h the behavioral (forced-swim-test and object-in-place test), as well as SERT MPC and neurochemical effects of CORT. These findings show that i.v. injections of Reelin have fast ATD-like effects associated with the restoration of hippocampal neurochemical deficits. Although additional mechanistic and pharmacokinetic studies are necessary, our data open the possibility to develop Reelin-based therapeutics with putative fast-ATD activity. Highlights: Repeated-CORT induced depression-like behavior and cognitive deficits. CORT altered the expression of hippocampal Reelin, and glutamate and GABA receptors. Reelin rescues behavioral and neurochemical abnormalities in male and female rats. Reelin normalized SERT membrane protein clustering in blood lymphocytes. The antidepressant-like effects of intravenous Reelin are fast-acting.